2009
DOI: 10.1002/pi.2710
|View full text |Cite
|
Sign up to set email alerts
|

Processing of continuous poly(amide‐imide) nanofibers by electrospinning

Abstract: Continuous poly(amide‐imide) nanofibers were fabricated using a novel electrospinning method with rotating and re‐collecting cylindrical collectors. The nanofilaments were modified using various post‐treatments, i.e. glycerol treatment and thermal imidization under tension, for possible application as high‐performance reinforcements. Morphological and mechanical properties of continuous poly(amide‐imide) nanofibers prepared by the electrospinning process and various post‐treatments were measured. Severe adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Since 1960's the webs of nano-fibers has been popularly made because of the instability of the electrospinning [9][10][11][12]. Recently, the modified elecrospinning to make the continuous and aligned nano-fibers has been developed by Korea Research Institute of Chemical Technology (KRICT) and followed by other institutes [13][14][15][16][17][18]. Recently the nano-diameter carbon fibers producing technologies by using the modified electrospinning attracted so many researchers [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1960's the webs of nano-fibers has been popularly made because of the instability of the electrospinning [9][10][11][12]. Recently, the modified elecrospinning to make the continuous and aligned nano-fibers has been developed by Korea Research Institute of Chemical Technology (KRICT) and followed by other institutes [13][14][15][16][17][18]. Recently the nano-diameter carbon fibers producing technologies by using the modified electrospinning attracted so many researchers [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Lee et al reported a method to optimize the fiber morphology and mechanical property (Lee et al, 2010). During the ES process of co-Poly-(amide)-imide (PAI), the fibers were soaked in glycerine.…”
Section: Fbappmentioning
confidence: 99%